(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
The journey of environmental auditing began in the USA in the early 1970s. An environmental impact assessment is defined as an assessment of the impacts of planned activities on the environment, biodiversity, vegetation and ecology, water, and air. Research objective was to elucidate the significance of collaborative synergies in executing EIA and Audits for environmental sustainability. The researcher applied the descriptive design in carrying out the survey in Laikipia County where a comprehensive review of literature review was done from relevant journals, conference and workshop papers, review papers, theses, books, reports, informative flyers/booklets and information available on the internet published by individual researchers, NEMA, NETFUND, UNEP and questionnaires were administered to 400 sampled respondents were the main sources of data for this paper. Findings revealed that 30% NEMA officials carried out environmental impact assessments during the planning phase; 20% UNEP Officials provided information via conferences, workshop papers, review papers, theses, books, reports, informative flyers/booklets & responded to questionnaires on significance of collaborative synergies in executing EIA & Audits for environmental sustainability and 20% Laikipia county residents took part in Public participation on the significance of collaborative synergies in executing EIA and Audits for environmental sustainability & responded to questionnaires. 20% of NETFUND officials disseminated information on EIA & Audit Case Studies. The researcher recommended environmental safeguarding measures such as, introduction of corporate environmental policies and strategies, adequate human and institutional capacity; environmental impact assessments during the planning phase.